2017
DOI: 10.21809/rilemtechlett.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Advances in dissolution understanding and their implications for cement hydration

Abstract: Recent advances in bridging kinetics and thermodynamics of mineral dissolution have opened new horizons in our understanding of the role of dissolution in cement hydration. Indeed most hydration kinetic regimes of alite can be rationally envisioned from a dissolution perspective. This short note reviews some key findings on dissolution mechanisms and their implication for cementitious systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Apparent activation energy (E a ) results and correlation coefficients (r 2 ) obtained from the fitting of a linearized Arrhenius equation at α = 0.5 for all pastes blended with C-S-H seeds. Nevertheless, it should be noted that some authors have proposed a two-step nonclassical nucleation process for C-S-H, where C-S-H would not serve as substrate for heterogeneous nucleation; thus, expecting that C-S-H will precipitate around the anhydrous grains even at high dosages of C-S-H seeds [26,29]. The effect of C-S-H seeds over the hydration kinetics was also studied through the setting and hardening processes.…”
Section: Tablementioning
confidence: 99%
“…Apparent activation energy (E a ) results and correlation coefficients (r 2 ) obtained from the fitting of a linearized Arrhenius equation at α = 0.5 for all pastes blended with C-S-H seeds. Nevertheless, it should be noted that some authors have proposed a two-step nonclassical nucleation process for C-S-H, where C-S-H would not serve as substrate for heterogeneous nucleation; thus, expecting that C-S-H will precipitate around the anhydrous grains even at high dosages of C-S-H seeds [26,29]. The effect of C-S-H seeds over the hydration kinetics was also studied through the setting and hardening processes.…”
Section: Tablementioning
confidence: 99%
“…In addition, gypsum (and other soluble sulfates salts as Na 2 SO 4 ) influence the C 3 S hydration. Gypsum retards the initial hydration of C 3 S, and a more extended induction period is observed [6,8,11,17]. According to Nicoleau et al [11] and Juilland et al [17] the sulfate ions are physically adsorbed on C 3 S surface, decreasing the surface charge and lowering its dissolution rate.…”
Section: Effect Of Calcium Sulfate On C 3 S Hydrationmentioning
confidence: 99%
“…Although not as heavily investigated as C 3 A-calcium sulfate systems, calcium sulfate also changes the C 3 S hydration, the morphology of its hydration products, and its mechanical strength [6,8,11,[17][18][19]. The effect of calcium sulfate on C 3 S hydration needs to be properly understood as it can influence the sulfate optimization in Portland cements and, therefore, can influence cement properties.…”
Section: Introductionmentioning
confidence: 99%
“…A direct experimental evidence showed that silicate dissolution is reduced by the presence of PCEs [131]. The fact that low dosages of polymer may effectively block the dissolution of a reactive phase may be understood from the perspective of blocking reactive surface areas on the surface, that are generally etch pits, or modifying the kinetics and the way they expand (Figure 16) [131,192]. As a confirmation, the exact same rate of reaction, and therefore retardation, was observed between a C3S with PCEs and the same C3S but annealed to remove defects on the surface [131].…”
Section: Pure C3s Phasesmentioning
confidence: 99%
“…a) Schematic representation of growth of etch pits in the absence and presence of PCEs adsorbed on the surface of tricalcium silicate close to the etch-pit, b) heat flows of a pure tricalcium silicate without and with PCE, and after annealing. Reproduced and adapted from [131] and [192].…”
Section: Pure C3s Phasesmentioning
confidence: 99%